Unemployment, life satisfaction and deprivation - Frasquilho, Diana (2017)
BACKGROUND: The economic recession produced a rapid rise of unemployment rates that was more visible in Southern European countries. There is evidence that unemployment correlates highly with individuals' poor life satisfaction. OBJECTIVE: To analyse the relationship between life satisfaction, household composition and socioeconomic deprivation in people facing unemployment during the economic recession. METHODS: A sample of 748 unemployed people from Lisbon (Portugal) completed a socio-demographic questionnaire, the Cantril's ladder of life scale, and the latent and manifest benefits of work scale (LAMB). Multiple regression analyses were used to test the associations between life satisfaction and all other variables. RESULTS: Partnered people report higher life satisfaction compared to singles. Financial deprivation and lack of structured time were the strongest factors negatively related to life satisfaction in both partnered and single people. Having children had a particular negative effect on the life satisfaction of partnered men; and living with an unemployed partner together with lack of social contact and high enforced activity had a negative effect on life satisfaction in partnered women. CONCLUSION: The heterogeneity of socioeconomic needs found by household composition bring practical policy implications for support actions targeting unemployed individuals in the unique context of economic recession.